Information for the single homeless and private tenants - London Irish Women's Centre, LIWC; Irish Women's Housing Action Group, IWHAG; Birtill, Angie (1995)
A 32-page printed booklet giving advice on finding a place to live in London and issues that may be encountered. An extensive appendix gives names, addresses and telephone numbers of many housing, homelessness and Irish community organisations. It was written by Angie Birtill of the London Irish Women's Centre (LIWC) and produced in conjunction with the Irish Women's Housing Action Group (IWHAG).